APLIKASI PEMET AAN DIGITAL CEPAT TANGGAPBENCANA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Rapid mapping applications today began milch done primarily for natllral disaster management. Role of digital maps (spatial information) in disaster management covering the entire series itself disasters ranging from pre-dllri/lg-post-disaster. The shapeof tllis spatial information is generally in thefoml of thematic maps, in addition to the basicmap asgeometricframe of reference,has afonn different shapesaccording to the disaster itself. This rapid mapping using GIS (Geographic Information System) as an instrullleut in map-making process, including spatial analysis problems associatedwith disasters such asdisaster areas,affectedareas,until the election of the evacuation rOllte and other infrastructu re disasters. This paper presentsfast mapping application basedon experiencesin order to participate and to map several areas affected by /latl/ral disasters dllring the period 2004-2006. The results of this rapid mapping are spatial information different both ti,e content and output of the maps. This is more dlle to the necessanjbasic /leedsof an mwlysis of the natl/ral disaster itself. Keyword: rapid mapping, GIS, thematic map, natllral disaster